The Salem witch showdown - Manning, Matthew K. (You choose. Scooby-Doo!, 2017)
"Witches are on the loose in Salem, and they're wreaking havoc at the annual costume contest! The Mystery Inc. gang is supposed to be judging the contest, but first they need your help to solve a spooktacular mystery and save the town. Will the gang choose the right path or find themselves at a dead end? Should they follow the witches or flee Salem for good? Will there ever be a costume contest winner?"-- Back cover.